A PRAGMATIC ANALYSIS OF SMILEYS EMOTICON IN WHATSAPP - Sholihatul Hamidah Daulay; Rahmadsyah Rangkuti; Afanin Nabila (Universitas Pamulang, 2023)
It is inevitable that all people around the world use WhatsApp nowadays. WhatsApp is the most popular app today in world wide. WhatsApp is the worldwide app that allows us to send message, voice notes, calls and video calls freely. It is available to make our journey in contacting and interacting with other people easy. WhatsApp has many features in its chat room, one of them is emoticon. Many emoticons in WhatsApp that appear to express our feelings and reactions toward something through chat. Those emoticons can also perform pragmatic function despite its function is to represent our feelings, thoughts, reaction or expression. This study was aimed to analyze the pragmatic value behind the smiley emoticons that people always use. This study was also aimed to investigate how people perceive the emoticon whether the way they use it is correct and related to the pragmatic function behind the emoticon. Because people tend to use the emoticon that is not suitable with the meaning behind it. This study is library research. The method used to conduct this study is descriptive qualitative. The result shows that many WhatsApp emoticon users do not perceive the emoticon they used properly based on pragmatic perspectives.